A pilot biomonitoring study of air pollution in the urban area of Sarajevo, Bosnia and Herzegovina: genotoxicity assessment in buccal cells. (19th September 2022) - Cetkovic, Tamara; Haveric, Anja; Behmen, Selma; Hadzic Omanovic, Maida; Caluk Klacar, Lejla; Dzaferspahic, Alen; Durmisevic, Irma; Mehanovic, Mahira; Haveric, Sanin
Abstract: Air pollution, recognized as a human carcinogen, is a significant cause of death in industrial and developing countries, and Bosnia and Herzegovina (B&H) is one of the leading countries for air pollution—caused death rate and has the poorest urban air quality in Europe. Despite a population decrease, urban air pollution in B&H has increased due to traffic pollution and still intensive use of solid fuel for heating and cooking. Human biomonitoring studies, regarding the described air pollution, have not been conducted before, and particularly have not been conducted in the region of Sarajevo. Good health, well-being, and environmental protection are part of the 17 defined Sustainable Development Global Goals. Accordingly, this study aimed to determine baseline levels of DNA damage in a group of Sarajevo citizens and to compare seasonal variations in DNA damage in relation to the reported levels of air pollution. From 33 individuals included in the study, samples were collected in the summer and winter seasons. The buccal micronucleus cytome (BMCyt) assay and comet assay in leucocytes isolated from saliva were performed. Mean values and standard deviations of log-transformed tail intensity (%), tail length (µm), and tail moment results in winter were 1.14 ± 0.23, 2.20 ± 0.14, and 1.03 ± 0.29, respectively, while in the summer season those values were 1.19 ± 0.19, 2.25 ± 0.17, and 1.07 ± 0.25, respectively. No significant differences were found for the comet assay parameters. Nevertheless, BMCyt results showed significant increases in micronuclei ( P = .008), binuclear cells ( P = .04), karyolysis ( P = .0003), condensed chromatin ( P = .03), and pyknosis ( P = .002) in winter. Although the results of comet and BMCyt assays are not in accordance, this study contributes to the human air pollution biomonitoring in Sarajevo, B&H, and based on the genotoxic effects of air pollution evidenced by the BMCyt biomarker further studies of this kind are necessary.